Covenant: A Vital Element of Reformed Theology Biblical, Historical and Systematic-Theological Perspectives - Burger, Hans; Kwakkel, Gert; Mulder, Michael (Brill, 2021)
Covenant: A Vital Element of Reformed Theology provides a multi-disciplinary reflection on the theme of the covenant, from historical, biblical-theological and systematic-theological perspectives. The interaction between exegesis and dogmatics in the volume reveals the potential and relevance of this biblical motif. It proves to be vital in building bridges between God's revelation in the past and the actual question of how to live with him today.